Multi-Site N-glycan mapping study 1: Capillary electrophoresis – laser induced fluorescence. Issue 1 (2nd January 2016) - Szekrényes, Ákos; Park, SungAe Suhr; Santos, Marcia; Lew, Clarence; Jones, Aled; Haxo, Ted; Kimzey, Michael; Pourkaveh, Shiva; Szabó, Zoltán; Sosic, Zoran; Feng, Peng; Váradi, Csaba; et al.
Abstract : An international team that included 20 independent laboratories from biopharmaceutical companies, universities, analytical contract laboratories and national authorities in the United States, Europe and Asia was formed to evaluate the reproducibility of sample preparation and analysis of N-glycans using capillary electrophoresis of 8-aminopyrene-1, 3, 6-trisulfonic acid (APTS)-labeled glycans with laser induced fluorescence (CE-LIF) detection (16 sites) and ultra high-performance liquid chromatography (UHPLC, 12 sites; results to be reported in a subsequent publication). All participants used the same lot of chemicals, samples, reagents, and columns/capillaries to run their assays. Migration time, peak area and peak area percent values were determined for all peaks with >0.1% peak area. Our results demonstrated low variability and high reproducibility, both, within any given site as well across all sites, which indicates that a standard N-glycan analysis platform appropriate for general use (clone selection, process development, lot release, etc.) within the industry can be established.